A study on work from home and employee productivity during covid19 pandemic in Malaysia - Lee, Shuh Xin (2022)
In global viewpoints, most of the countries was facing the COVID-19 pandemic outbreak in the almost same period. The purpose of this study is to see how working from home impacts workers' work-life balance during COVID-19. This research has 5 independent variables and one dependent variables. The independent variables are work from home, work-life balance, work stress, job satisfaction and technical perspective. However, the dependent variable would be employee productivity. There are 9 hypotheses being tested in this research. However, there are 2 hypotheses was not supported which are Work from Home has significance influence on Work Stress during COVID-19 and Work Stress has significance influence on Employee Productivity during COVID-19. A total of 230 respondents was gathered using quantitative approach which is questionnaire to fill the gaps by investigating several factors which affected employee productivity while working from home during COVID-19 pandemic. The responses are being analyzed using SPSS software. The study has revealed that work from home, work-life balance, job satisfaction and technical perspective has effects on employee productivity. In theoretical implications has shown that most of the studies does not show same results as this study. However, organizations should practically implies the suggestions as their employees work from home to improve their productivity.